The Ergonomic Elderly Gym Improving Physical Fitness and Increasing The Bone Mass of The Elderly - Ariati, N.N.; Adiputra, N.; Tirtayasa, K.; Adiatmika, I.P.G.; Pangkahila, A.; Sutjana, I.D.P; Bakta, I.M.; Manuaba, I.B.P; Sutajaya, I.M. (Universitas Atma Jaya Yogyakarta, 2019)
The public is increasingly aware of the importance of exercise for the elderly because exercise is an option to reduce complaints due to setbacks and improve the health of the elderly. In fact the implementation in the field is often wrong as in Banjar Benaya which implements routine exercises only once a week with a duration less than 30 minutes, does not pay attention to nutritional needs, does not use sports clothing, and displays that are not clear. The measurement of elderly physical fitness is still relatively low. Based on these problems, improvements were made to the application of ergonomic elderly gymnastics due to improve elderly’s physical fitness and increase the bone mass. This study used a treatment by subject design conducted in April 2017-August 2018. The target population was all elderly in Denpasar and the affordable population was determined by multistage random sampling then selected Banjaya Benaya Peguyangan Village with a sample of 20 people who met the inclusion criteria. The data collection were physical fitness and bone mass. The difference in treatment effects were analyzed using a Paired Sample t-Test with α = 0.05 for data with normal distribution and Wilcoxon test, α = 0.05 for data with abnormal distribution. Data showed that there were differences in physical fitness improvement in Period I and Period II after 8 weeks of gymnastics at 43.43% with very bad categories being bad, the difference in increase in whole body bone mass was 16.76% and leg bone mass 68.67%. Analysis of Paired Sample-t-Test physical fitness data and Wilcoxon test for bone mass data in Period I and Period II after gymnastics for 8 weeks, found that there was a significant difference (p <0.05). It can be concluded that ergonomic elderly gym can significantly improve physical fitness and increase bone mass of the elderly. It is recommended that the elderly continue to exercise with a duration of 30-45 minutes, the frequency of 3 times a week to maintain elderly’s physical fitness.